Islamic law and international human rights law - Emon, Anver M.; Ellis, Mark S.; Glahn, Benjamin (Oxford : Oxford University Press, 2013)
Deepening the discussion of the relationship between Islamic law and human rights, this volume gathers leading experts in both fields to examine how each system protects and limits fundamental freedoms. From gender equality to freedom of religion it explores the debate, examining the operation of the law in context.
Description based on online resource; title from PDF title page (viewed on Oct. 30, 2012).
Keywords: Islamic law; Human rights -- Religious aspects -- Islam